Preferences Of Future Cooking Fuel Types Among Urban And Peri-Urban Households In Greater Accra Region Of Ghana: Business-As-Usual Or Sustainable Pathways?. - Bawakyillenuo, S.; Agbelie, I.S.K.; Crentsil, A.O.; Danquah, S.K. (Energy Policy, 2025)
Women and children in Ghana face risks such as burns, poisoning, and injuries from using solid biomass fuels like charcoal and firewood for cooking. Although LPG is the dominant modern cooking fuel, electricity remains less commonly used. In the Greater Accra Region, 70% of households rely on LPG for cooking, while 23% and 3% use charcoal and firewood, respectively. This study examines the future cooking fuel preferences of households in Ga East, Ga West, and Adenta Municipalities, using data from 1200 urban and peri-urban households collected through a mixed-method approach. Findings reveal that LPG is expected to remain the preferred cooking fuel over the next five years, followed by charcoal, with electricity ranked third. These future preferences reflect current practices, indicating a continuation of existing trends. However, 7.3% of households expressed interest in adopting e-cooking technologies, such as Electric Pressure Cookers (EPC), if these technologies become more accessible and affordable. This suggests a potential shift toward sustainable cooking practices. To promote the adoption of e-cooking technologies, critical policy measures focused on education, affordability, and technology availability are necessary. Such initiatives could support a transition to environmentally sustainable cooking solutions in the Greater Accra Region.
Research Article
Keywords: Sustainable; Future; Fuel preferences; e-cooking; Biomass; LPG